PENGARUH ORGANISATION CITIZENSHIP BEHAVIOR, PERILAKU INOVATIF, KREATIFITAS INDIVIDUAL, DAN LOYALITAS TERHADAP KINERJA KARYAWAN DI PT TARINDO - Riyanto, Sigit; Sutrisno, Sutrisno; Qristin Violinda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to analyze the effect of Organizational Citizenship Behavior, Innovative Behavior, Individual Creativity, and Loyalty on Employee Performance at PT Tarindo. The benefit of this research is that this research can be used as input in developing and determining the right Human Resource Management strategy in order to get results that optimize employee performance in the company. The population of researchers is all employees of PT Tarindo with a total of 86 employees, with a total sample of 86 respondents of PT Tarindo using non probability sampling techniques; saturated sampling (census). The results of the analysis and discussion show that partially Organizational Citizenship Behavior has a positive and significant effect on Employee Performance, Innovative Behavior has a positive and significant effect on Employee Performance, Individual Creativity has a positive and significant effect on Employee Performance, and Loyalty has a positive and significant effect on Employee Performance at PT Tarindo